Recent Advances in Herbal Medicines for Digestive System Malignancies - Sheng, Jiyao; Zou, Xiaohan; Cheng, Ziqian; Xiang, Yien; Yang, Wei; Lin, Yang; Cui, Ranji (Frontiers in Pharmacology, 2018)
Herbal medicine, as an important part of traditional Chinese medicine, have been used to treat digestive system malignancies for many years, and have gradually gained recognition worldwide. The role of herbal medicines in the comprehensive treatment of digestive system malignancies is being improved from adjuvant treatment of the autologous immune function in cancer patients, to the treatment of both the symptoms and disease, direct inhibition of tumor cell growth and proliferation, and induction of tumor cell autophagy and apoptosis. Their specific mechanisms in these treatments are also being explored. The paper reviews the current anti-tumor mechanisms of traditional Chinese medicine, including single herbal medicines, Chinese herbal formulations, Chinese medicine preparations and Traditional Chinese medicine extract, and their application in the comprehensive treatment of digestive system tumors, providing a reference for clinical application of traditional Chinese medicine.